Hipparcos, the New Reduction of the Raw Data - van Leeuwen, Floor. (Astrophysics and Space Science Library, 2007)
The new reduction of the Hipparcos data presents a very significant improvement in the overall reliability of the astrometric catalogue derived from this mission. Improvements by up to a factor 4 in the accuracies for in particular brighter stars have been obtained. This has been achieved mainly through careful study of the satellite dynamics, and incorporating results from these studies in the attitude modelling. Data correlations, caused by attitude-modelling errors in the original catalogue, have all but disappeared. This book provides overviews of the new reduction as well as on the use of the Hipparcos data in a variety of astrophysical implementations. A range of new results, like cluster distances and luminosity calibrations, is presented. The Hipparcos data provide a unique opportunity for the study of satellite dynamics. The orbit covered a wide range of altitudes, showing in detail the different torques acting on the satellite. One part of the book details these studies and their impact on the new reduction. It furthermore presents an extensive summary on a wide range of spacecraft and payload calibrations, which provide a detailed record of the conditions under which these unique Hipparcos data have been obtained.